2015
DOI: 10.4103/0366-6999.149200
|View full text |Cite
|
Sign up to set email alerts
|

Footprint Mismatch of Cervical Disc Prostheses with Chinese Cervical Anatomic Dimensions

Abstract: Background:The footprint of most prostheses is designed according to Caucasian data. Total disc replacement (TDR) has been performed widely for cervical degenerative diseases in China. It is essential to analyze the match sizes of prostheses footprints and Chinese cervical anatomic dimensions in our study.Methods:The anatomic dimensions of the C4–C7 segments of 138 patients (age range 16–77 years) in a Chinese population were measured by computed tomography scans. We compared the footprints of the most commonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…One study found a large discrepancy between footprints of prostheses and Chinese cervical anatomic data in 414 segments. 18 In the present study, measurements of 400 segments produced similar results.…”
Section: Discussionsupporting
confidence: 82%
“…One study found a large discrepancy between footprints of prostheses and Chinese cervical anatomic data in 414 segments. 18 In the present study, measurements of 400 segments produced similar results.…”
Section: Discussionsupporting
confidence: 82%
“…[ 11 , 12 ] In fact, there is a large mismatch of available parameters of disc prostheses, as well as Chinese cervical anatomic data: 17.03% to 57.61% in the anterior–posterior diameter and 35.51% to 94.93% in the center of mediolateral diameter. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…The arcuate surface of the novel prosthesis can provide a greater effective contact area between the prosthesis and cervical endplate, in order to disperse the axial load more evenly. Second, the novel prosthesis is designed according to the anatomy of cervical vertebra and the people’s physical size of the cervical disc in China [ 14 , 15 ], providing a better size match between the prosthesis and cervical vertebra. Size match between the prosthesis and cervical vertebra can not only provide a greater contact area between the prosthesis and cervical endplate but also can cover the peripheral marginal zones of cervical endplate which provide a much stronger support than the central areas [ 11 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, size mismatch in the current available cervical disc prostheses is another noteworthy issue, since an undersized prosthesis is unable to cover the peripheral marginal zones of the endplate whose biomechanical strength is much larger than that of the central areas so as to increase the probability of prosthesis subsidence [ 11 13 ]. Therefore, according to the anatomy of cervical vertebra and the people’s physical size of cervical disc in China [ 14 , 15 ], we designed a novel artificial disc prosthesis (Pretic-I, Trauson) based on the physiological curvature of cervical endplate, with an advantage of increasing the contact area between the prosthesis and endplate to disperse the axial load.…”
Section: Introductionmentioning
confidence: 99%